The added value of a portable gamma camera for intraoperative detection of sentinel lymph node in squamous cell carcinoma of the oral cavity: A case report - Mayoral, M.; Paredes, P.; Sieira, R.; Vidal-Sicart, S.; Marti, C.; Pons, F. (Revista espanola de medicina nuclear e imagen molecular, 2014)
The use of sentinel lymph node biopsy in squamous cell carcinoma of the oral cavity is still subject to debate although some studies have reported its feasibility. The main reason for this debate is probably due to the high false-negative rate for floor-of-mouth tumors per se. We report the case of a 54-year-old man with a T1N0 floor-of-mouth squamous cell carcinoma who underwent the sentinel lymph node procedure. Lymphoscintigraphy and SPECT/CT imaging were performed for lymphatic mapping with a conventional gamma camera. Sentinel lymph nodes were identified at right Ib, left IIa and Ia levels. However, these sentinel lymph nodes were difficult to detect intraoperatively with a gamma probe owing to the activity originating from the injection site. The use of a portable gamma camera made it possible to localize and excise all the sentinel lymph nodes. This case demonstrates the usefulness of this tool to improve sentinel lymph node detecting in floor-of-mouth tumors, especially those close to the injection area. La biopsia del ganglio centinela en el carcinoma escamoso de la cavidad oral es un tema controvertido aunque varios estudios hayan demostrado su viabilidad, probablemente por la elevada tasa de falsos negativos en los tumores del suelo de la boca. Presentamos el caso de un hombre de 54 años con carcinoma escamoso del suelo de la boca T1N0 que se sometió al procedimiento del ganglio centinela. Se realizaron imágenes linfogammagráficas y de SPECT/TC con una gammacámara convencional. Se identificaron ganglios centinela en los niveles Ib derecho, IIa izquierdo y Ia, siendo difíciles de localizar intraoperatoriamente con una gammasonda dada la actividad procedente del lugar de inyección. Usando una gammacámara portátil se pudieron localizar y resecar todos los ganglios centinela. Este caso muestra la utilidad de esta herramienta para mejorar la detección del ganglio centinela en los tumores del suelo de la boca, especialmente en aquellos próximos al área de inyección.